2007
DOI: 10.1037/0096-3445.136.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Is time-based prospective remembering mediated by self-initiated rehearsals? Role of incidental cues, ongoing activity, age, and motivation.

Abstract: The present research examined self-reported rehearsal processes in naturalistic time-based prospective memory tasks (Study 1 and 2) and compared them with the processes in event-based tasks (Study 3). Participants had to remember to phone the experimenter either at a prearranged time (a time-based task) or after receiving a certain text message (an event-based task) and record the details of occasions when they thought about this intention during a 7-day delay interval. The rehearsal and retrieval of time-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
265
6
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(295 citation statements)
references
References 85 publications
19
265
6
1
Order By: Relevance
“…An interesting follow-up question concerns whether these spontaneous retrieval processes can be turned off by instructing participants that their prospective memory task is finished. Whether spontaneous retrieval processes can be deactivated is an important question, because prospective memory retrieval has been demonstrated during ongoing task contexts that have no embedded prospective memory task (Experiment 1), which implies that one retrieves intentions even when it is unnecessary to do so (see Kvavilashvili & Fisher, 2007, for a similar finding in a naturalistic study). However, it would be maladaptive if irrelevant (i.e., finished) intentions constantly popped into mind whenever an old cue appeared.…”
Section: Methodsmentioning
confidence: 69%
“…An interesting follow-up question concerns whether these spontaneous retrieval processes can be turned off by instructing participants that their prospective memory task is finished. Whether spontaneous retrieval processes can be deactivated is an important question, because prospective memory retrieval has been demonstrated during ongoing task contexts that have no embedded prospective memory task (Experiment 1), which implies that one retrieves intentions even when it is unnecessary to do so (see Kvavilashvili & Fisher, 2007, for a similar finding in a naturalistic study). However, it would be maladaptive if irrelevant (i.e., finished) intentions constantly popped into mind whenever an old cue appeared.…”
Section: Methodsmentioning
confidence: 69%
“…In this context, time-based tasks have been considered to be more difficult to remember than event-based tasks, because they lack an external event that signifies the opportunity for recall and require more self-initiated processing for monitoring the time (e.g. Einstein et al 1995;Kvavilashvili and Fisher 2007). Accordingly, Einstein and McDaniel (1990) proposed that event-based prospective memory tasks might not produce large age effects, while time-based tasks might be more likely to produce age-related deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ihle et al (2012) also found no age-related difference in importance ratings for real prospective memory tasks, although again their young adult sample consisted of ''mostly'' undergraduate students. Thus, research has shown two null results for age effects on importance ratings for real-life prospective memory tasks despite prior demonstrations of the effect for experimenterassigned tasks (e.g., Kvavilashvili and Fisher 2007;Patton and Meit 1993). Therefore, additional research on age-related differences on real-life prospective memory tasks is warranted.…”
Section: Predictions For Young Versus Older Adultsmentioning
confidence: 97%
“…For example, compared to young adults, older adults score higher on levels of conscientiousness (e.g., Soto et al 2011) and report more goals focused on generativity (e.g., Do more work on quilts for the needy; Penningroth and Scott, 2012). Studies using experimenter-assigned naturalistic tasks (e.g., mailing postcards or making a phone call) have found that older adults rate the task as more important than younger adults do (e.g., Kvavilashvili and Fisher 2007;Patton and Meit 1993). In fact, motivational differences between young adults and older adults have been posited as a key factor in explaining the ''age prospective memory paradox'' (e.g., Phillip et al 2008).…”
Section: Predictions For Young Versus Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation